COMO O ENGAJAMENTO INFLUENCIA O EFEITO DO CONTEÚDO GERADO PELA MARCA NA INTENÇÃO DE USO DO CONSUMIDOR? UM ESTUDO NO MERCADO CULTURAL - Fantino, Ana Paula Gusmao (2022)
To understand brand communication online with its audience, in order to generate behavior of use of cultural spaces, this study examined the influence of the content generated by the brand on the intention to use the physical space, in a relationship mediated by engagement and intention of Instagram usage and moderated by consumer cultural capital. In the consumer-brand relationship, the production of highquality content improves the visibility of the space on social networking sites. Such content, which can be informative, entertainment or even incentives (with remuneration or discounts), generate interest on the part of the follower, increasing their level of engagement. This relationship plays a key role in the intention to use Instagram profiles of cultural spaces, impacting the intention to use the physical spaces themselves (museums, art galleries and other exhibition spaces). Thus, the engagement of followers of a cultural space on Instagram directly influences their intention to use the space, either in the virtual context (where the consumer follows and interacts with the profile on the social networking site), or in the physical environment (increasing the chances that this behavior will result in a visit to the architectural space). This sequence of relationships explains how the contents generated by cultural spaces on social networks influence the behavior of intention to use the physical space itself by the follower. In this sense, we understood that the opportunities for conviviality that individuals had to maintain themselves in environments that provide contact with culture can be a decisive factor of a greater or lesser degree of engagement with cultural spaces. Therefore, this study also considers a moderating variable capable of better explaining the individual and his condition of being more or less engaged with a space: cultural capital. Thus, this study proposes a theoretical model of how the content produced by a cultural space can impact consumer engagement on social networking sites, influencing the consumer-brand relationship. We tested a model that integrates content types and engagement consequences, analyzing how art consumers’ intention to use cultural spaces is affected. Results show that cultural capital will positively moderate the relationship between consumer engagement and the intention to use the cultural space, so that the direct effect is stronger when the individual’s cultural capital is high. Through a survey, with the data analyzed using the SmartPLS software, the theoretical hypotheses proposed were evidenced. The results show that engagement and intention to use Instagram have a mediating effect on the intention to use the space; so, relationship that will be strengthened to higher levels of the individual’s cultural capital. As a theoretical contribution, this study is a pioneer in relating the Theory of Cultural Capital to the Theory of Consumer Engagement with the Brand, proposing a conceptual model for analyzing consumer engagement of different types of content generated by the cultural space in Instagram posts. In addition, the results also pointed to management suggestions, indicating insights for the construction of strategies that influence consumer engagement in the online environment, specifically in cultural contexts.